Structured visual analysis of single‐case experimental design data: Developments and technological advancements. Issue 2 (28th December 2021) - Dowdy, Art; Jessel, Joshua; Saini, Valdeep; Peltier, Corey
Abstract : Visual analysis is the primary method used to interpret single‐case experimental design (SCED) data in applied behavior analysis. Research shows that agreement between visual analysts can be suboptimal at times. To address the inconsistent interpretations of SCED data, recent structured visual‐analysis technological advancements have been developed. To assess the extent to which structured visual analysis is used to guide or supplement applied behavior analysts' interpretation of SCED graphs, a systematic review between the years of 2015 to 2020 in the Journal of Applied Behavior Analysis was conducted. Findings showed that despite recent efforts to develop structured visual‐analysis tools and criteria, these methods are rarely used to analyze SCED data. An overview of structured visual‐analysis tools is shared, their utility is delineated, common characteristics are brought to light, and future directions for both research and their clinical use are highlighted.